Elevated glucose impairs endothelium-dependent relaxation by activating protein kinase C. - Tesfamariam, B (1991)
A possible relationship between protein kinase C activation and impaired receptor-mediated endothelium-dependent relaxation in diabetes mellitus was examined in isolated aorta from normal rabbit exposed to elevated glucose. Aorta treated for 10 min with 4-phorbol 12-myristate 13-acetate (PMA), a protein kinase C activator, showed decreased relaxations to the endothelium-dependent vasodilator, acetylcholine, similar to normal aorta exposed to elevated glucose (22 and 44 mM) for 6 h. Relaxations to the receptor-independent endothelium-dependent vasodilator, A23187, and those caused by the direct smooth muscle vasodilator, sodium nitroprusside, were unaffected by treatment with PMA or exposure to elevated glucose. Indomethacin increased relaxations to acetylcholine of aorta treated with PMA indicating a role for vasoconstrictor prostanoids. PMA caused a significant increase in basal and acetylcholine-stimulated release of vasoconstrictor prostanoids including thromboxane A2 from aortic segments with, but not without endothelium. Protein kinase C inhibitors, H-7 or sphingosine, restored the abnormal acetylcholine-induced relaxations as well as suppressed the abnormal release of prostanoids in aorta exposed to elevated glucose. These findings suggest that the dysfunction of receptor-mediated endothelium-dependent relaxation associated with exposure to elevated glucose is due to increased production of vasoconstrictor prostanoids by the endothelium as a consequence of protein kinase C activation.